A Literature Review on Urban Usability and Accessibility to Investigate the Related Criteria for Equality in the City - Pinna, Francesco; Garau, Chiara; Annunziata, Alfonso (Computational Science and Its Applications - ICCSA 2021, 2021)
The environmental issues and, in recent years, the Covid-19 pandemic determined an increasing consensus around the need for urban policies aimed at re-shaping the urban realm. The issue of equality and the related conditions of accessibility and usability emerge as critical requirements in the re-shaping of the urban landscape and mobility. As a consequence, the proposed article discusses a comprehensive literature review on the topics of usability and accessibility and of the complementary notions of disability and exclusion. The objectives of the literature review are to define a taxonomy of the different dimensions of usability and accessibility, to assess the relevance of the different forms of usability and accessibility across disciplinary fields related to urban and transportation studies, to identify the co-relations among specific aspects of urbanity and mobility and conditions of accessibility and usability. The proposed literature review is the preliminary stage of a study aimed at defining a methodological framework for quantitatively describing the urban environment in terms of its accessibility and usability. The proposed defines the theoretical framework of an analysis method for evaluating inequality incorporated into the urban environment and for facilitating smart decisions and holistic design in the context of urban planning.